An Analysis Of Student’s Anxiety In Speaking English At The Eighth Semester Students Of English Education Department In Panca Sakti University - Arthania Primastuti Putrinda; Iswandini Agustin (PT. Inovasi Teknologi Komputer, 2023)
This study aims to identify the factors that contribute to this anxiety, exploring its causes and expressions. This research seeks to provide a more detailed understanding of students' challenges when speaking English through collected qualitative data, questionnaire surveys, and insights gained from interviews. This research presents an analysis of student anxiety in speaking English to understand activities surrounding student anxiety in speaking English. This research uses qualitative data from a questionnaire survey and insights gathered through interviews to highlight various factors that contribute to student anxiety. The results of the study concluded that most of the eighth semester students of the English Language Education Department experienced test anxiety. The level of student reaction is also suggested to be three types of anxiety. As many as 30% of students feel communication anxiety, 40% feel anxiety about taking exams because they are afraid of getting a bad grade, and 30% feel afraid of negative evaluations because they are worried. There are 6 (six) factors that contribute to student anxiety, such as feeling insecure and embarrassed, afraid of feeling guilty, feeling less than others, afraid and nervous, not understanding what the teacher is saying, worrying if other students are like them.